Sub-10 nm gold nanoparticles promote adipogenesis and inhibit osteogenesis of mesenchymal stem cells. Issue 7 (31st January 2017) - Li, Jingchao; Chen, Ying; Yang, Yingjun; Kawazoe, Naoki; Chen, Guoping
Abstract : Sub-10 nm Au NPs with an average size of 4 nm (Au4-mPEG NPs) had a promotive effect on the adipogenic differentiation and an inhibitive effect on the osteogenic differentiation of human bone marrow-derived mesenchymal stem cells (hMSCs) due to the highly induced ROS level. Abstract : Sub-10 nm gold nanoparticles (Au NPs) have attracted extensive attention for different biomedical applications because of their small size. However, the influence of small NPs on the differentiation of human bone marrow-derived mesenchymal stem cells (hMSCs) is unclear. In this study, 4 nm small Au NPs (Au4-mPEG NPs) were synthesized to investigate their influence on the osteogenic and adipogenic differentiation of hMSCs and 40-nm counterparts (Au40-mPEG NPs) were used for comparison. Different from Au40-mPEG NPs, Au4-mPEG NPs reduced the ALP activity, calcium deposition and osteogenic marker gene expression, while increased the oil droplet formation and adipogenic marker gene expression in hMSCs. The mechanism study indicated that Au4-mPEG NP treatment did not affect the cellular mechanical property significantly but induced a high level of reactive oxygen species (ROS). The results provide some insights into the influence of sub-10 nm Au NPs on the stem cell functions and applications of these small particles for tissue engineering.